A theory of strategic venture investing - Hellmann, Thomas (Journal of Financial Economics, 2002)
Some venture capital investors seek purely financial gains while others, such as corporations, also pursue strategic objectives. The paper examines a model where a strategic investor can achieve synergies, but can also face a conflict of interest with the entrepreneur. If the start-up is a complement to the strategic partner, it is optimal to obtain funding from the strategic investor. If the start-up is a mild substitute, the entrepreneur prefers an independent venture capitalist. With a strong substitute, syndication becomes optimal, such that the independent venture capitalist is the active lead investor and the strategic partner a passive co-investor. The expected returns for the entrepreneur are nonmonotonic, lowest for a mild substitute, and higher for a strong substitute as well as for a complement. The paper also explains why a strategic investor often pays a higher valuation than an independent venture capitalist.